Doping and phase segregation in Mn2+- and Co2+-doped lead halide perovskites from 133Cs and 1H NMR relaxation enhancement. Issue 5 (15th January 2019) - Kubicki, Dominik J.; Prochowicz, Daniel; Pinon, Arthur; Stevanato, Gabriele; Hofstetter, Albert; Zakeeruddin, Shaik M.; Grätzel, Michael; Emsley, Lyndon
Abstract : Lead halide perovskites belong to a broad class of compounds with appealing optoelectronic and photovoltaic properties. Abstract : Lead halide perovskites belong to a broad class of compounds with appealing optoelectronic and photovoltaic properties. Doping with transition metal ions such as Mn 2+ and Co 2+ has recently been reported to substantially enhance luminescence and stability of these materials. However, so far atomic-level evidence for incorporation of the dopants into perovskite phases has been missing. Here, we introduce a general and straightforward method for confirming the substitutional doping of bulk perovskite phases with paramagnetic dopants. Using 133 Cs and 1 H solid-state MAS NMR relaxation measurements we provide for the first time direct evidence that, consistent with current understanding, Mn 2+ is incorporated into the perovskite lattice of CsPbCl3 and CsPbBr3 and does not form clusters. We also show that, contrary to current conviction, Co 2+ is not incorporated into the perovskite lattice of MAPbI3 .